2021
DOI: 10.1371/journal.pone.0250430
|View full text |Cite
|
Sign up to set email alerts
|

Asthma severity as a contributing factor to cancer incidence: A cohort study

Abstract: Background A putative link between asthma and asthma severity with the occurrence of cancer has been suggested but has not been fully investigated. The objective of this study is to assess the incidence of all types of cancer in a cohort of asthmatic patients. Methods and findings A single center cohort retrospective study was conducted to investigate the role of asthma as a potential risk factor for various cancers. Participants were followed for a period of 9 years from 01/01/2010 to 30/12/2018 and cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Interestingly, the histopathology of asthma, lung cancer, and asthma with lung cancer suggests that asthma and lung cancer exhibit similar molecular mechanisms and pathways for the progression and/or increased risk of lung cancer in severe asthma. This association was recently shown to be the case using epidemiological data linking the two diseases [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the histopathology of asthma, lung cancer, and asthma with lung cancer suggests that asthma and lung cancer exhibit similar molecular mechanisms and pathways for the progression and/or increased risk of lung cancer in severe asthma. This association was recently shown to be the case using epidemiological data linking the two diseases [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 91%
“…A single-center study conducted by us at Rashid Hospital, Dubai, demonstrated that asthmatic patients had a higher risk of developing tumors related to the breast, colon, lung, and prostate. Lung cancer in asthmatics had the longest diagnosis period (36.6 years), while prostate cancer had the shortest (16.5 years) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous retrospective cohort study found that asthma patients had a long diagnostic duration for lung cancer, with a mean of 36.6 years. [ 54 ] Moreover, asthma severity considerably increased the likelihood of developing cancer in asthmatic individuals (HR 2.929, 95% CI 1.784–4.907). [ 54 ] In addition, a prospective study of adults with partially controlled asthma had a higher risk of lung cancer (HR 1.39, 95% CI 1.00–1.92) compared with healthy groups, while no increased risk was observed in the well-controlled group (HR 0.91, 95% CI 0.54–1.52).…”
Section: Discussionmentioning
confidence: 99%
“…[ 54 ] Moreover, asthma severity considerably increased the likelihood of developing cancer in asthmatic individuals (HR 2.929, 95% CI 1.784–4.907). [ 54 ] In addition, a prospective study of adults with partially controlled asthma had a higher risk of lung cancer (HR 1.39, 95% CI 1.00–1.92) compared with healthy groups, while no increased risk was observed in the well-controlled group (HR 0.91, 95% CI 0.54–1.52). [ 52 ] Uncontrolled asthma is more prone to a decline in Forced Expiratory Volume in the first second (FEV1), similar to the Chronic Obstructive Pulmonary Disease (COPD) phenotype, and a decline in FEV1 significantly increases the risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most symptomatic patients have advanced disease at the time of diagnosis [20]. In our study, the clinical presentation was dominated by numerous symptoms and clinical signs, with variable incidences, whose were similar to that reported in the literature for: cough (8-75%) [21], dyspnea (3-60%) [22], expectoration (70-78%) [23], hemoptysis (6-35%) [21], weight loss (0-68%) [24], pallor (0-31.6%) [25], cyanosis (22.7%) [26], lack of appetite (57-61%) [20], chest pain (20-49%) [20], fever (0-20%) [23], and wheezing (0-2%) [27]. The comparative analysis of the incidence of the symptoms and clinical signs encountered in the two LC patients' groups showed no statistically significant differences for most of the clinical features encountered.…”
Section: The Clinical Studymentioning
confidence: 99%